2021
DOI: 10.3390/ijerph18168562
|View full text |Cite
|
Sign up to set email alerts
|

Uganda Mountain Community Health System—Perspectives and Capacities towards Emerging Infectious Disease Surveillance

Abstract: In mountain communities like Sebei, Uganda, which are highly vulnerable to emerging and re-emerging infectious diseases, community-based surveillance plays an important role in the monitoring of public health hazards. In this survey, we explored capacities of village health teams (VHTs) in Sebei communities of Mount Elgon in undertaking surveillance tasks for emerging and re-emerging infectious diseases in the context of a changing climate. We used participatory epidemiology techniques to elucidate VHTs’ perce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 53 publications
(61 reference statements)
1
5
0
Order By: Relevance
“…These are important factors that relate with health service access. This result is similar to that in other studies that have shown community health care workers within this area to perceive climate change to undermine their activities [9]. Although the target population are different, similar results have been…”
Section: Perception Of Climate Change and Diseasessupporting
confidence: 90%
See 2 more Smart Citations
“…These are important factors that relate with health service access. This result is similar to that in other studies that have shown community health care workers within this area to perceive climate change to undermine their activities [9]. Although the target population are different, similar results have been…”
Section: Perception Of Climate Change and Diseasessupporting
confidence: 90%
“…This result can be linked to the results of the current study as the study area is a hard-to-reach area with limited opportunities for ensuring sustained health systems. This has been demonstrated in other studies that indicate limited surveillance capacities partly because of the terrain and limited infrastructure and communication channels [9].…”
Section: Satisfaction With Health Services Deliverymentioning
confidence: 56%
See 1 more Smart Citation
“…However, the existing surveillance systems (both YF passive and sentinel surveillance systems) for human population in Uganda face significant challenges such as inadequate laboratory diagnostic capabilities, a shortage of skilled public health professionals such as those needed for data analysis and interpretation of surveillance data, leading to the underreporting of YF cases, and slower outbreak response [48]. Moreover, health workers and community-based surveillance volunteers often lack awareness of the YF case definition, leading to ineffective and irregular reporting of cases at both community and health facility levels [49]. Consequently, only few healthcare units report YF cases [17].…”
Section: Suspected Casementioning
confidence: 99%
“…Despite having a village health team (VHT) network for community disease surveillance, volunteers are challenged by inadequate access to transportation for surveillance data collection; lack of data analysis and storage capacity; no coordination among environmental, wildlife, or livestock surveillance; and inability to use mobile phones for data reporting. 24 Experts' engagement with communities is essential for early recognition and response to emerging infectious disease events. While Uganda has formalized a National One Health Platform for advising government agencies and coordinating their responses to zoonotic diseases, this endeavor lacks financial backing and actual intersectoral coordination.…”
Section: Convergence and Diseasementioning
confidence: 99%